2007
DOI: 10.1176/appi.ap.31.5.380
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Theater: An Innovative Method for Experiential Learning of Psychiatric Symptomatology Using Modified Role-Playing and Improvisational Theater Techniques

Abstract: Headspace Theater may serve as a useful tool for helping various learners to experientially understand what a person may encounter when under the influence of a mental health condition, and thus help shape attitudes and increase empathy toward such people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…In 2006, 83% either somewhat agreed, agreed, or strongly agreed with the statement: ''The 'improv' training did improve my communication skills. '' In 2007, that number increased to 90%. The proportion of students who agreed that their communication skills improved due to training showed no difference from one year to the next (p 5 0.175).…”
Section: Discussionmentioning
confidence: 92%
“…In 2006, 83% either somewhat agreed, agreed, or strongly agreed with the statement: ''The 'improv' training did improve my communication skills. '' In 2007, that number increased to 90%. The proportion of students who agreed that their communication skills improved due to training showed no difference from one year to the next (p 5 0.175).…”
Section: Discussionmentioning
confidence: 92%
“…There is an extensive body of research demonstrating that role-play and simulation can be very effective tools in teaching psychiatry (Barney and Shea, 2007; McNaughton et al, 2008), and others have specifically advocated experiential training through actors in role-play situations (Ballon et al, 2007), although the effectiveness of these approaches have not been formally tested over a prolonged period. Similarly, others have shown that it is possible to improve empathy using actors who are role-playing being patients, and that these improvements last at least 1 month (Walters et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To further facilitate understanding, practitioner–resident interactions observed in earlier qualitative studies (Kontos, 2004, 2006) were translated by a playwright into prescripted role‐plays that were enacted by study participants. Role‐plays were intended to simulate the experience of impairment, evoke understanding and foster empathy (Ballon et al. , 2007).…”
Section: Methodsmentioning
confidence: 99%